Material Paduan Berbasis Aluminida untuk Aplikasi Suhu Tinggi di Sektor Penerbangan dan Luar Angkasa - Umara, Yunita; Rizki, Ilham; Cahaya, Natasya Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This research focuses on the development of aluminide-based alloy materials for high-temperature applications in the aviation and aerospace sectors. Aluminide alloys, such as TiAl and NiAl, are known for their excellent oxidation resistance and mechanical properties at high temperatures, but still face challenges regarding toughness at room temperature. This research aims to optimize alloy composition and manufacturing methods, particularly through additive manufacturing approaches, to enhance material performance under extreme conditions. The methods used include alloy composition design, fabrication using powder metallurgy and additive manufacturing, as well as mechanical property and oxidation resistance testing. The research results indicate that the addition of alloying elements such as Nb and Mo can improve oxidation resistance and microstructural stability at high temperatures. This research also contributes to the development of the material research ecosystem in Indonesia and can support self-reliance in the production of high-temperature materials for the aviation and aerospace sectors.